Advances in microalgal lipid extraction for biofuel production: a review. (21st August 2018) - Harris, Jesse; Viner, Kelsey; Champagne, Pascale; Jessop, Philip G.
Abstract: Algal biomass is an attractive feedstock for sustainable biofuel production because of its high growth rate and the fact that it does not compete with food crops. This review examines progress made in the processing and extraction of microalgal lipids as feedstocks for algae‐derived biofuels. The discussion focuses on lipid extraction processes but also mentions drying, cell disruption, and transesterification processes because of their potential effect on the extraction process, and because of the possibility of performing them simultaneously with extraction. Some of the common themes discussed include the benefits of utilizing wet microalgal biomass, combining process steps (process intensification), and the importance of considering the entire life cycle when assessing the 'greenness' of a technology. Lipid extraction technologies will need to be improved for microalgal biofuels to compete effectively with fossil fuels, particularly through the development of energy‐efficient extraction methods and the adaptation of these methods for large‐scale production. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd